Confident Friends proyect: helping others makes us better. (Journal of Parents and Teachers, 2014)
The Association of Friends of Trust, a group of sixth grade students starts on an adventure to create a project to help other children in the school and thus become better themselves. The "thugs" can be heroes.We learn that freedom involves responsibility and we learn to appreciate the consequences.
Keywords: Creative and cooperative learning; cinema and education in values; methodological innovation; education; experiences